Creative Economy Development: Government Efforts and the Use of Digital Media for MSMEs in East Java - Cahyo Tri Atmojo; Saiful Aminudin Al Kusuma Putra; Yudhi Ferdi Andri Asmawan (Institut Teknologi dan Bisnis Asia Malang, 2026)
The purpose of this study is to identify government efforts that have been carried out through the interview and documentation process, especially for the government through the Cooperative and MSMEs service, to identify the use of digital media, to identify the impact of government efforts and the use of digital media, to identify the impact of government efforts and the use of digital media by MSMEs in the field of Batik Crafts by MSMEs. The method used by the researchers was a qualitative approach. The research findings indicate that the government's efforts to develop the creative economy are supported by training facilitated by the department, and the district government, through the Cooperatives, MSMEs, and Trade Department, also provides assistance in business management, including the use of digital media. The research findings on the use of digital media by MSMEs indicate that artisans and entrepreneurs have utilized digital media for marketing activities, with Instagram and TikTok being the most common. Research findings related to the impact of government efforts and the use of digital media can be seen to have a positive impact, namely, it can further improve the competence or quality of artisans in the digital world.